2018
DOI: 10.1186/s12983-018-0286-5
|View full text |Cite
|
Sign up to set email alerts
|

The seasonal sensitivity of brown bear denning phenology in response to climatic variability

Abstract: BackgroundFor brown bears (Ursus arctos), hibernation is a critical part of the annual life cycle because energy savings during hibernation can be crucial for overwintering, and females give birth to cubs at that time. For hibernation to be a useful strategy, timing is critical. However, environmental conditions vary greatly, which might have a negative effect on the functionality of the evolved biological time-keeping. Here, we used a long-term dataset (69 years) on brown bear denning phenology recorded in 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…However, no significant correlations were detected between den entry/exit and snow depth (Delgado et al, 2018;Judd et al, 1986).…”
Section: Influence Of Environmental Factorsmentioning
confidence: 82%
See 4 more Smart Citations
“…However, no significant correlations were detected between den entry/exit and snow depth (Delgado et al, 2018;Judd et al, 1986).…”
Section: Influence Of Environmental Factorsmentioning
confidence: 82%
“…Moreover, the increased climatic variability could make the weather patterns that govern the seasonality of animal life cycles to some extent more unpredictable for many organisms, including bears (Weiskopf et al, 2020). Actually, these interannual fluctuations in hibernation chronology due to climatic conditions have already been reported in both American black bears (Miller, Smith, Auger, Black, & Allphin, 2017) and brown bears (Delgado et al, 2018;Evans et al, 2016;Friebe et al, 2014;McLoughlin, Case, et al, 2002;. reported that for each 4°C increase in spring temperature brown bear den exit occurs 10 days earlier.…”
Section: Discussion and Con Clus I On Smentioning
confidence: 99%
See 3 more Smart Citations